Danny Lane : Breaking Tradition. - Bourdon House London (London : Mallett & Son (Antiques) Ltd., 1999)
Much of Danny Lane's work is made to commission, sometimes sculpture, sometimes furniture, occasionally lighting. This type of work enables Danny to develop new ideas, taking into account the situation in which the object will be placed. Indeed many of the new works in this exhibition took into account Mallett's specific requirements, especially with regard to lighting.
History of glass furniture p. 63
biog., coll. p. 62
Engels
Danny Lane : Breaking Tradition, Bourdon House London, 28th April- 22nd May 1999
boek
Keywords: Lane, Danny